An evaluation of offshore wind power production by floatable systems: A case study from SW Portugal. (15th July 2017) - Pacheco, A.; Gorbeña, E.; Sequeira, C.; Jerez, S.
Abstract: The challenge for floating offshore wind structures is to reduce costs. The industry needs a wind turbine support solution that can be fabricated and deployed from existing shipyards and port facilities, while investors need accurate estimations and forecasts of wind resources and quantified information on the inherent variability in wind power generation. This paper merges hindcast model data with observed in situ data to characterize the wind resource potential off the SW coast of Portugal. The validation procedure adopted allows an estimation of the coefficient used for power-law extrapolation of the wind measurements and a reduction in the uncertainty of the power density calculations. Different types of turbine model are compared and site metocean characteristics are examined as a basis for choosing between existing wind floatable solutions. The calculations using four different wind turbine models indicate a preferable installed capacity of 3–4 MW for a hub height of 90–120 m (i.e., representing the best capacity factor and load hours). There is a consistent difference in power density of about 20% from a location 5 nautical miles (NM) offshore to one 10 NM offshore, which represents an increment of 20%–25% in energy production depending on the particular wind turbine capacity factor. Highlights: Offshore wind resource assessed for SW Portugal using hindcast and in situ data. Non-validated power-law exponents result in inaccurate wind resource assessments. Wind turbine devices are compared based on capacity factor and energy production. Power density varies for different offshore locations. Energy production depends mainly on wind turbine capacity factor and less on diameter or hub height.